1985
DOI: 10.1002/jlac.198519850915
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen von Peptidalkaloiden, 11. Über Aminosäuren und Peptide, 51. — Dehydroaminosäuren, 19. Totalsynthese von Hexaacetylcelenamid A

Abstract: Es wird die Totalsynthese des linearen Peptidalkaloids Hexaacetylcelenamid A (7) beschrieben. Schlüsselreaktionen sind zwei Kondensationen mit α‐(Dialkylphoshoryl)aminosäurederivaten 10 zum Aufbau der Dehydroaminosäure‐ und Dehydropeptidderivate 14 bzw. 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…27 As an alternative, concentrated hydrochloric acid or dry hydrogen chloride was added to the reaction mixture just after filtering off the catalyst. 27,45 In situ derivatization of amino ketones was accomplished by adding acetic anhydride 61 or di-tert-butyl dicarbonate (Boc anhydride) 48 to the solution of the substrate prior to the hydrogenation. Acetylation 61 or aroylation by an active ester 49 immediately after the reduction has also been reported.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 As an alternative, concentrated hydrochloric acid or dry hydrogen chloride was added to the reaction mixture just after filtering off the catalyst. 27,45 In situ derivatization of amino ketones was accomplished by adding acetic anhydride 61 or di-tert-butyl dicarbonate (Boc anhydride) 48 to the solution of the substrate prior to the hydrogenation. Acetylation 61 or aroylation by an active ester 49 immediately after the reduction has also been reported.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…Acetylation 61 or aroylation by an active ester 49 immediately after the reduction has also been reported. Hydrogenation in the presence of Pd-C was performed most often in alcohols (methanol or ethanol), 16,27,54,63 acetic acid 27,61 or 1,4-dioxane 48,49 have also been applied in some cases. The reported yields of the desired a-amino ketones were usually good (65-94%).…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…7). When Cbz-protected phosphonate 20 (Schmidt et al 1982, 1984; Schmidt and Wild 1985; Hamzavi et al 2003) was employed in the Wittig-Horner reaction with aldehyde 10 , Cbz-protected δ-azido-didehydro α-amino acid ester ( Z )- 21 was obtained in 81 % yield (calculated as traces of aldehyde 10 could not completely be removed). Stereoisomer ( E )- 21 could also be isolated in 3 % yield, and again, application of the established 1 H NMR criteria for the distinction of ( Z )- and ( E )-didehydro amino acids (Mazurkiewicz et al 2005) confirmed the stereochemical assignment.…”
Section: Resultsmentioning
confidence: 99%
“…They have been employed in the synthesis of peptide natural products, e.g. azinomycins A and B, 14 (AE)-tunichrome An-1, 15 tunichromes Mm-1 and Mm-2, 16 hexaacetylcelenamide A, 17,18 clionamide, 19 etc. Also, some compounds of this class are effective glutathione transferase inhibitors.…”
Section: Introductionmentioning
confidence: 99%